2018
DOI: 10.1111/imb.12549
|View full text |Cite
|
Sign up to set email alerts
|

Two sphingomyelin synthase homologues regulate body weight and sphingomyelin synthesis in female brown planthopper, N. lugens (Stål)

Abstract: Although sphingomyelins known to be are lipid constituents of the plasma membrane in vertebrates, much remains obscure about the metabolism of sphingomyelins in insects. With ultra performance liquid chromatography‐time‐of‐flight‐tandem mass spectrometry analysis, we revealed for the first time that sphingomyelins are abundant in Nilaparvata lugens (Stål), the brown planthopper (BPH), and their biosynthesis is carried out by sphingomyelin synthase‐like protein 2 (SMSL2), which is homologous to sphingomyelin sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…growth, apoptosis and differentiation; Acharya et al, 2008). Sphingomyelin has important structural and functional roles in the cell (Ramstedt and Slotte, 2002), and its concentration can affect the bodyweight of brown planthopper (Shi et al, 2019). Previous studies have indicated that B. subtilis can maintain the health and promote the growth and development of silkworm (Wang et al, 2019;Yeruva et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…growth, apoptosis and differentiation; Acharya et al, 2008). Sphingomyelin has important structural and functional roles in the cell (Ramstedt and Slotte, 2002), and its concentration can affect the bodyweight of brown planthopper (Shi et al, 2019). Previous studies have indicated that B. subtilis can maintain the health and promote the growth and development of silkworm (Wang et al, 2019;Yeruva et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the lipid biosynthetic process, sphingolipids are an important class of lipids that participate in crucial events of cell proliferation, differentiation, and apoptosis in various species [ 46 ]. Recently, evidence has accumulated to show that sphingolipids have roles in the signaling pathways involved in reproduction and oocyte development of N. lugens [ 47 , 48 , 49 ]. Cyclin-dependent kinase (CDK) is a serine/threonine protein kinase family that cooperates with cyclin and is required for embryo development and cell cycle progression [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Figure S1). Shi et al, 2019 demonstrated that dsRNA-mediated knockdown of N. lugens sphingomyelin synthase-like protein 1, which is involved in sphingolipids metabolism, led to increased weight of females, but not of males, suggesting a general sex specific effect of lipid metabolism modulation in planthoppers. In C. elegans, XPO1 silencing resulted in elevated lipid accumulation and increased expression of lipases (Silvestrini et al, 2018).…”
Section: Severe Obesity Observed In Pmxpo1-knockdown Femalesmentioning
confidence: 96%